Proposed Business Strategy for New Business in Muslim Fashion Industry (Case Study: QUIN) (The Indonesian Journal of Business Administration, 2021)
In the era of a competitive market, starting a new business might be demanding and challenging. A company can have a low position in an attractive industry and better than a company with the right place in an unattractive industry. Indonesia is the top three countries with a massive expenditure on Muslim apparel. The popularity of Muslim fashion and hijab in Indonesia has shown a significant increase (Global Business Guide Indonesia, 2016). QUIN is a newcomer in fashion industry from Bandung that engaged in the textile trade for the Muslim hijab in Indonesia. QUIN offers a product that elevates religious values combined with an element of beauty. The increasing number of hijab brands, a massive amount of fabric suppliers and vendors is one proof of Bandung as a potential city to start a fashion business. To build a new business, QUIN needs a proper business strategy due to the high competition in Muslim fashion industry in Indonesia. This paper analyzed the external environment through Customer analysis, Competitor analysis, and Porter's Five Forces analysis. Meanwhile, the internal analysis uses analysis of the Business Process and VRIO analysis. Based on internal and external analysis, Value Proposition Canvas and Business Model Canvas are used to develop the appropriate business strategy for QUIN. Keywords: Business Model Canvas, Hijab Industry, Moslem Fashion, Proposed Business Strategy